Agglomeration and emigration: The economic impact of railways in post-Famine Ireland - Alan Fernihough; Ronan C. Lyons (Queen's University Centre for Economic History (QUCEH), 2022)
Ireland developed one of the world's most intensive railroad networks in the second half of the 19th century. However, the emergence of railroads occurred in tandem with a failure to industrialize and mass depopulation suggesting limited, if any, impact on the island's economy. This paper examines this claim from a trade-based market-access perspective. Matching high-resolution geospatial data for nearly 3,400 districts to existing road and waterway networks as well as Ireland's nascent railroad network, we quantify the extent of market access improvements caused by rail. Additionally, we compute an external market access measure that accounts for improved access to international ports. Our findings reveal that this distinction is vital. Improvements in domestic market access brought about by railroads had a substantial positive influence on both population density and land values, while better access to ports had the opposite, negative, effect. Overall, these conflicting forces largely cancel out, hiding rail's importance. However, a supplementary analysis reveals that the introduction of rail fostered a significant reorientation within the economy across two key domains: emigration and the labour-intensiveness of agriculture. Areas with relatively more access to ports experienced greater levels of emigration and a faster switch from labor-intensive tillage to pastoral farming-with differential access explaining around two-fifths of the observed shift in both variables between the Great Famine and the Great War.
Keywords: N14; N94; O18; R12; R4; 330; Ireland; Railways; Market Access; Emigration